A Flavonoid Glycoside Compound from Siraitia grosvenorii with Anti-Inflammatory and Hepatoprotective Effects In Vitro - Juanjiang Wu; Huaxue Huang; Limin Gong; Xing Tian; Zhi Peng; Yizhun Zhu; Wei Wang (Biomolecules)
Inflammation is a pivotal factor in the development and advancement of conditions like NAFLD and asthma. Diet can affect several phases of inflammation and significantly influence multiple inflammatory disorders. Siraitia grosvenorii, a traditional Chinese edible and medicinal plant, is considered beneficial to health. Flavonoids can suppress inflammatory cytokines, which play a crucial role in regulating inflammation. In the present experiments, kaempferol 3-O-α-L-rhamnoside-7-O-β-D-xylosyl(1→2)-O-α-L-rhamnoside (SGPF) is a flavonoid glycoside that was first isolated from S. grosvenorii. A series of experimental investigations were carried out to investigate whether the flavonoid component has anti-inflammatory and hepatoprotective effects in this plant. The researchers showed that SGPF has a stronger modulation of protein expression in LPS-induced macrophages (MH-S) and OA-induced HepG2 cells. The drug was dose-dependent on cells, and in the TLR4/NF-κB/MyD88 pathway and Nrf2/HO-1 pathway, SGPF regulated all protein expression. SGPF has a clear anti-inflammatory and hepatoprotective function in inflammatory conditions.